Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy